SINTHESIS AND TRANSFORMATIONS OF 2-BROM-4-ALKOXYMETHYLBUTANOLIDS (Proceedings of the YSU B: Chemical and Biological Sciences, 2006)
A new method for obtaining 2-brom-4-alkoxymethylbutanolids has been offered. The method provides high yields. The interaction of bromlactones with potassium rhodanide has been investigated.
Keywords: new method; 2-brom-4-alkoxymethylbutanolids; bromlactones